Epidemiology of Surgical Treatment of Adolescent Sports Injuries in the United States: Analysis of the MarketScan Commercial Claims and Encounters Database - Nicholas Bonazza, M.D.; Dallas M. Smuin, M.D.; Nicholas Sterling, M.D., Ph.D.; Djibril Ba, M.P.H.; Guodong Liu, Ph.D.; Douglas L. Leslie, Ph.D.; William Hennrikus, M.D.; Aman Dhawan, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2019)
Purpose: To determine whether there is increasing surgical management of adolescent sports injuries and whether the average age of surgical patients is decreasing. Methods: The Truven Health MarketScan Database was searched from 2008 to 2014 for patients 10 to 19 years of age using the International Classification of Disease, 9th Revision codes and Current Procedure Terminology, 4th Edition, codes for operative treatment for the following conditions: anterior cruciate ligament (ACL) injuries, knee collateral ligament (KCL) injuries, meniscal injuries, Osgood–Schlatter syndrome, and elbow ulnar collateral ligament injuries. Patients identified were characterized by sex, age, year of injury, and type of residence (urban vs rural) based on metropolitan statistical areas. Results: A total of 516,892 patients sustained 1 of the identified injuries, and 133,541 (25.8%) patients underwent a related surgery. KCL and meniscal injuries demonstrated a consistent increase in the rate of surgical intervention (P < .0001). Average age of surgical intervention did not increase or decrease overall for any diagnosis. Female adolescents were more likely to undergo surgery for KCL injuries (adjusted odds ratio [aOR] 1.7, 95% confidence interval [CI] 1.58-1.79, P < .0001), Osgood–Schlatter syndrome (aOR 1.8, 95% CI 1.38-2.39, P < .0001), and ACL injuries (aOR 1.5, 95% CI 1.45-1.52, P < .0001), whereas male adolescents were more likely to undergo surgery for meniscal injuries (aOR 1.3, 95% CI 1.24-1.30, P < .0001) and ulnar collateral ligament injuries (aOR 1.1, 95% CI 1.06-1.23, P < .0005). Patients in rural areas were more likely to undergo surgical intervention for ACL and meniscal injuries (P < .0001) and KCL injuries (P = .02). Conclusions: We found that surgical treatment of 5 common sports injuries remains stable, with only KCL injuries and meniscal injuries showing an increase in surgical incidence. Average age of surgical intervention did not change significantly over the 7-year time span for any diagnosis. Level of Evidence: Level IV, Cross Sectional Study.